Dairy Based Farming: Economic Analysis for Viable Livelihood Opportunity for Jhum Practicing Tribal People of Mizoram State - Sangpuii, Lalrin; Malhotra, Ravinder (International Journal of Bio-resource and Stress Management, 2023)
Jhum cultivation in North Eastern Region of India is traditionally practiced by local tribes. This practice accounts almost 84% of total shifting cultivation area of India. Of late, this system becomes a serious threat to the livelihoods opportunity and environmental security in the region. Keeping this in view, the present study was conducted to explore the contribution of crops towards income generation both under Jhum condition and integrated crops-cattle farming condition in three districts of Mizoram in the year 2014–15. Usual farm management techniques were applied to assess the profitability. Cost of crop cultivation in Jhum was estimated to be Rs. 23778 ha-1 while in case of integrated farming it was worked out to be Rs. 38886 ha-1. The income generated from crop under dairy-based farming (Rs. 41906 ha-1) was found to be much higher than the income obtained from crops in Jhum farming (Rs. 23581 ha-1) implying that dairy-based farming was more profitable compared to Jhum farming. Jhum could be profitable if family labour engagement was the practice. The ha-1 cost of cattle maintenance was found to be ` 66711 while the gross return was estimated to be Rs. 72332. The B:C ratio for dairy-based farm was found to be more than 1(one) indicating the profitability of this type of farming. In addition, the integrated crops-cattle farming had higher potentiality to afford farm employment. It is, thus, suggested to provide necessary support to make this system more adopted by the tribal people of Mizoram for its economic viability.